The culture and art of death in 19th century America - Lightfoot, D. Tulla (McFarland & Company, Inc., Publishers, 2019)
Nineteenth-century Victorian-era mourning rituals--long and elaborate public funerals, the wearing of lavishly somber mourning clothes, and families posing for portraits with deceased loved ones--are often depicted as bizarre or scary. But behind many such customs were rational or spiritual meanings. This book offers an in-depth explanation at how death affected American society and the creative ways in which people responded to it. The author discusses such topics as mediums as performance artists and postmortem painters and photographers, and draws a connection between death and the emergence of three-dimensional media.